Un aménagement de berge antique sur l’Auron, pour la villa de Lazenay à Bourges (Cher) - Alain Ferdière; Emmanuel Marot (Gallia)
About fifty years ago, rescue excavations carried out during the archaeological survey of a sector of the Auron valley threatened by the construction of the “Auron lake” uncovered remarkable developments on the banks of this watercourse, immediatly upstream from Bourges/Avaricum, capital of the territory of the Bituriges Cubi. They are part of the very vast archaeological complex of the “Lazenay” site occupied from Protohistory to the Middle Ages, more particularly linked to the large villa that developed in this area between the 1st c. BC and Late Antiquity. The port development consists of a “quay” with a wooden frame and a rubble stone structure, forming the corner of a small basin set back from the left bank of the Auron river. It may have been established in the first third of the 1st c. BC and may have lasted for only half a century. Recent discoveries made in the peri-urban sector of Bourges made it possible to better situate this facility in its economic and social context, in connection with this large villa and its monumental development. However, this riverbank development and the monumentalisation that it provides to this riverside villa also highlight the significant commercial role of the city of Bourges –the port on the Yèvre river according to the etymology of Avaricum–, in the centre of Gaul, the main boundary between the eastern and the western part of Gaul. the Yèvre river, of which the Auron river is a tributary, provides a connection with the Cher river and a connection between the Rhône-Saône axis and the lower Loire valley by avoiding the long detour of the Loire bend passing through Orléans/Cenabum.